Penile Hemodynamic Response to Phosphodiesterase Type V Inhibitors after Cavernosal Sparing Inflatable Penile Prosthesis Implantation: A Prospective Randomized Open-Blinded End-Point (PROBE) Study - Adham Zaazaa; Michaela Bayerle-Eder; Ramzy Elnabarawy; Mahmoud Elbitar; Taymour Mostafa (Advances in Urology)
Forceful corporal dilatation amidst penile prosthesis implantation may injure cavernosal arteries compromising penile vasculature. In this study, we aimed to compare the conventional and cavernosal sparing techniques regarding cavernosal artery preservation. Overall, 33 patients underwent inflatable penile prosthesis implantation with Coloplast Titan Touch® three-piece inflatable penile implants. 16 patients had conventional implantations with serial vigorous dilatations, while 17 patients were implanted with the cavernosal sparing technique, consisting of a single minimal corporal dilatation after an intraoperative intracavernosal injection (ICI) of Alprostadil. Postoperatively, a penile duplex Doppler ultrasound study was performed. Whenever a cavernosal artery was spared and thus successfully probed, its hemodynamics were studied before and after an oral administration of a phosphodiesterase type 5 inhibitor (PDE5i). A cavernosal artery was successfully probed in 16/17 (94%) of patients in the cavernosal sparing group compared to 5/16 (31%) of patients in the conventional group with a significant statistical difference (P=0.001). This demonstrated that the cavernosal sparing technique was superior to the conventional approach in preserving the cavernosal artery (odds ratio 35.2, 95% IC 3.5–344.2; P=0.0022). Whenever a cavernosal artery could be probed, its hemodynamic responsiveness was also preserved. This trial is registered with NCT03733860.